If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x(4-6)=10
We simplify the equation to the form, which is simple to understand
3x(4-6)=10
Simplifying terms in parentheses
3x*(-2)=10
Reorder the terms in parentheses
+(-6x)=10
Remove unnecessary parentheses
-6x=+10
We move all terms containing x to the left and all other terms to the right.
-6x=+10
We simplify left and right side of the equation.
-6x=+10
We divide both sides of the equation by -6 to get x.
x=-1.66666666667
| 4b=88 | | 21x+13=3x-5 | | f+25=81 | | 3c=75 | | .5(10y+4)=17 | | e+53=73 | | 7e=147 | | 4b+6y^2=0 | | 4b+6y^2= | | y+9=21 | | 2x-2=3x-2 | | -5y+6x=21 | | 9x=7x+12 | | a-4.5+2a=7+17a+4 | | -5x+6y=21solvey | | 2z+3=6z+9 | | 8x^2=800 | | 9x-2x=7 | | -5x+6y=21 | | x+22=41 | | 6b=-102 | | 2z+1=6z+9 | | 11x-5x=12 | | 5x+3.1=9.6 | | y-55=62 | | 4x+64=-4x | | 4x+64=-4z | | y+18=45 | | x=0.65x+385 | | 9x+8x=0 | | 10x-3x=7 | | x=0.65+385 |